Overexpression of Fatty Acid Amide Hydrolase Induces Early Flowering in Arabidopsis thaliana - Teaster, Neal D.; Keereetaweep, Jantana; Kilaru, Aruna; Wang, Yuh-Shuh; Tang, Yuhong; Tran, Christopher N.; Ayre, Brian G.; Chapman, Kent D.; Blancaflor, Elison B. (Frontiers in Plant Science, 2012)
N-Acylethanolamines (NAEs) are bioactive lipids derived from the hydrolysis of the membrane phospholipid N-acylphosphatidylethanolamine (NAPE). In animal systems this reaction is part of the “endocannabinoid” signaling pathway, which regulates a variety of physiological processes. The signaling function of NAE is terminated by fatty acid amide hydrolase (FAAH), which hydrolyzes NAE to ethanolamine and free fatty acid. Our previous work in Arabidopsis thaliana showed that overexpression of AtFAAH (At5g64440) lowered endogenous levels of NAEs in seeds, consistent with its role in NAE signal termination. Reduced NAE levels were accompanied by an accelerated growth phenotype, increased sensitivity to abscisic acid (ABA), enhanced susceptibility to bacterial pathogens, and early flowering. Here we investigated the nature of the early flowering phenotype of AtFAAH overexpression. AtFAAH overexpressors flowered several days earlier than wild type and AtFAAH knockouts under both non-inductive short day (SD) and inductive long day (LD) conditions. Microarray analysis revealed that the FLOWERING LOCUS T (FT) gene, which plays a major role in regulating flowering time, and one target MADS box transcription factor, SEPATALLA3 (SEP3), were elevated in AtFAAH overexpressors. Furthermore, AtFAAH overexpressors, with the early flowering phenotype had lower endogenous NAE levels in leaves compared to wild type prior to flowering. Exogenous application of NAE 12:0, which was reduced by up to 30% in AtFAAH overexpressors, delayed the onset of flowering in wild type plants. We conclude that the early flowering phenotype of AtFAAH overexpressors is, in part, explained by elevated FT gene expression resulting from the enhanced NAE hydrolase activity of AtFAAH, suggesting that NAE metabolism may participate in floral signaling pathways.